Impacto del proceso de convergencia de las NIIF en las empresas del departamento de Boyacá periodo 2014-2016 (2018)
The market in Colombia has been transformed in the last decades into an international business center, accompanied by commercial integration with the different economic blocs of the hemisphere. Boyacá companies as the main agents of business in the region, have not been alien to this reality, since the process of standardization of international financial reporting standards (NIFF), has become part of international standards with global instruments whose objective is to generate financial statements, with unified accounting systems, more compressible for the users of the information, and which consequently helps to make investment decisions and developed local businesses.The main challenges faced in the preparation and presentation of financial information should be aimed at adapting and using the current international accounting system. It can be concluded that the accounting differences have marked a constant need to seek unification alternatives, so that the reconciliation processes between the internal accounting regulations of a country compared to the international one, does not affect the economic criteria with which a transaction should be measured Financial.